Hukum Perkawinan Campuran dan Hak Atas Tanah di Indonesia - Ketut Oka Setiawan (Jurnal Hukum dan Demokrasi (JHD), 2023)
Mixed marriage in Law No. 1 of 1974 (UUP) is a marriage between two people who in Indonesia are subject to different laws, because of differences in nationality and one of the parties is a foreign citizen and one of the parties is an Indonesian citizen (Article 57 UUP). Based on this statement, according to the UUP, mixed marriage regulations prohibit brides and grooms from different religions. The prohibition is mentioned indirectly in Article 2 paragraph (1) of the UUP, "marriage is valid if it is carried out according to the laws of each religion". If a husband and wife buy a piece of land after their marriage, it will automatically become the property of both of them (husband and wife), based on the provisions of Article 35 paragraph (1) of the UUP. However, if at the time or before the marriage takes place, they make a marriage agreement with separate assets, their ownership becomes each of the husband/wife (Article 29 yo 35 UUP). In mixed marriages referred to in Article 57 UUP, namely a marriage between two people who in Indonesia are subject to different laws, because of differences in nationality and one party is a foreign citizen and one party is an Indonesian citizen, it does not change their citizenship status, still for Indonesian citizens in this case their rights are limited and they are not even given the opportunity to become subjects of HM, HGU and HGB, if at the time or before their marriage they do not make a marriage agreement with separate assets. According to the law, a marriage agreement can only be made at or before the marriage, in other words a marriage agreement cannot be made after the marriage.